Validation of the Portuguese version of the Pittsburgh Sleep Quality Index (PSQI-PT). (January 2017) - Del Rio João, Karine Alexandra; Becker, Nathália Brandolim; de Neves Jesus, Saul; Isabel Santos Martins, Rute
Abstract: The present study was realised to validate the Portuguese version of the PSQI. The instrument PSQI-PT was applied to 347 Portuguese community-dwelling adults aged 18–69 years old. The resulting data was used to perform the psychometric analysis to validate the instrument. No structural modifications to the questionnaire were necessary during the adaptation process. The scores for the PSQI-PT showed an adequate internal consistency. The principal component analysis (PCA) produced good factor loading for all items. Finally, the analysis of demographic variables showed that age and literacy influence the values for the "Global Sleep Quality" (GSQ) in this Portuguese sample. In conclusion, this study demonstrated that the PSQI-PT is a valid and reliable instrument for the assessment of sleep quality with the advantage of allowing community-dwelling adults differentiation between good and poor sleepers. Highlights: It is proposed the validation of the Portuguese version of the PSQI. The PSQI-PT score had an overall reliability coefficient (Cronbach's α) of 0.70. This questionnaire showed adequate psychometric proprieties. The PSQI-PT is a valid and reliable instrument to assess the sleep quality. The PSQI-PT assesses the sleep quality of clinical and non-clinical populations.